13th International Energy Conversion Engineering Conference 2015
DOI: 10.2514/6.2015-3903
|View full text |Cite
|
Sign up to set email alerts
|

Design, Qualification and Integration Testing of the High-Temperature Resistance Temperature Device for Stirling Power System

Abstract: The Advanced Stirling Radioisotope Generator (ASRG), developed from 2006 to 2013 under the joint sponsorship of the United States Department of Energy (DOE) and National Aeronautics and Space Administration (NASA) to provide a high-efficiency power system for future deep space missions, employed Sunpower Incorporated's Advanced Stirling Convertors (ASCs) with operating temperature up to 840 °C. High-temperature operation was made possible by advanced heater head materials developed to increase reliability and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The acceptance of accuracy is correlated with accuracy level. The RTD correlation can predict the accepted temperature with acceptable accuracy [31]. In many applications, the necessity of accuracy comes with the focus on each of repeatability and stability of the sensor, therefore, the features of stability and repeatability are often confused with the accuracy level, but the important thing is to understand the difference between them in order to choose type of metal to application purpose in designated location.…”
Section: Rdts Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…The acceptance of accuracy is correlated with accuracy level. The RTD correlation can predict the accepted temperature with acceptable accuracy [31]. In many applications, the necessity of accuracy comes with the focus on each of repeatability and stability of the sensor, therefore, the features of stability and repeatability are often confused with the accuracy level, but the important thing is to understand the difference between them in order to choose type of metal to application purpose in designated location.…”
Section: Rdts Accuracymentioning
confidence: 99%
“…The analysis from [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] in above section (5. Methods and materials) will summarized as in table 2.…”
Section: Basic Characteristicsmentioning
confidence: 99%
“…By using the thermal bridge, the RTD is not exposed to the full hot-end temperature, but it is able to project hot-end temperature for monitoring purposes. 5 Convertor dimensional inspection uncovered some small dimensional changes that point to the possibility that the RTD thermal bridge could be influencing heater head geometry. However, a detailed review of the data showed that the dimensional biases towards the RTD thermal bridge seen with ASC-E3 #2 preceded the installation of the RTD thermal bridge, and the changes simply grew over time.…”
Section: A Heat Collector Crowningmentioning
confidence: 99%